Nickel catalysts supported on gadolinium-doped ceria for IT-SOFC applied in methane steam reforming - Andrade, Maria Luiza (2014)
The anode materials used in IT-SOFC consist of a mixture of nickel and cerium oxide doped with rare earth, forming a composite with a conductor metal and a ceramic with ionic conductivity. Nickel catalysts (30 wt %) supported on gadolinium-doped ceria (10 and 20% mol/mol) were prepared in this work, in order to obtain materials with catalytic properties suitable for using them as anodes in IT-SOFC. The catalysts were evaluated in steam reforming of methane in the range from 600 to 750ºC, using H2O/C ratio of 1:1 and 3:1. It was noted that gadolinium caused an increase of metal-support interaction and resistance to sintering of metal particles. The most promising catalyst was that of 30% Ni and 10% Gd (30CG10). Although the carbon content is not reduced, the carbon deposited in 30CG10 catalyst is more reactive due to its amorphous nature and therefore, it is possible to regenerate at temperature lower than 400°C.